2001
DOI: 10.1104/pp.127.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Functional Conservation of Plant Secondary Metabolic Enzymes Revealed by Complementation of Arabidopsis Flavonoid Mutants with Maize Genes

Abstract: Mutations in the transparent testa (tt) loci abolish pigment production in Arabidopsis seed coats. The TT4, TT5, and TT3 loci encode chalcone synthase, chalcone isomerase, and dihydroflavonol 4-reductase, respectively, which are essential for anthocyanin accumulation and may form a macromolecular complex. Here, we show that the products of the maize (Zea mays) C2, CHI1, and A1 genes complement Arabidopsis tt4, tt5, and tt3 mutants, restoring the ability of these mutants to accumulate pigments in seed coats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…As previously described (Dong et al, 2001), a single spot corresponding to cyanidin was observed, which was absent in tt5 seedlings (Supplemental Fig. S1A).…”
Section: Novel Fluorescent Properties Of Arabidopsis Anthocyaninsmentioning
confidence: 73%
“…As previously described (Dong et al, 2001), a single spot corresponding to cyanidin was observed, which was absent in tt5 seedlings (Supplemental Fig. S1A).…”
Section: Novel Fluorescent Properties Of Arabidopsis Anthocyaninsmentioning
confidence: 73%
“…4A), indicating the accumulation of tannins in seed coats. In addition, these transgenic seedlings showed anthocyanin pigments in cotyledons and hypocotyls when germinated in medium devoid of nitrogen sources, a sensitive condition previously employed to induce the anthocyanin biosynthesis pathway in Arabidopsis (Hsieh et al, 1998;Dong et al, 2001). In contrast, seed coats of SbCHS8-expressing tt4 plants remained yellow in both T 1 and T 2 generations and the transgenic seedlings failed to accumulate anthocyanin under nitrogen deficiency (Fig.…”
Section: Transgenic Analysis Of Arabidopsis Transparent Testa Mutantsmentioning
confidence: 92%
“…The complementation of Arabidopsis transparent testa (tt) mutants by maize genes demonstrated the convenience of this system for establishing the function of uncharacterized coding sequences with homology to flavonoid structural genes (Dong et al, 2001). Arabidopsis tt4 mutants are deficient in CHS activities, resulting in the absence of flavonoid-derived metabolites in different tissues.…”
Section: Transgenic Analysis Of Arabidopsis Transparent Testa Mutantsmentioning
confidence: 99%
“…The activation of biosynthetic genes in metabolic pathways is often coordinated by transcription factors. Chalcone synthase (CHS) and chalcone isomerase (CHI) are two early pathway enzymes that drive the flavonoid pathway toward the formation of naringenin, the common precursor of many flavonoid compounds including anthocyanins, flavones, and phlobaphenes (Dong et al 2001;Winkel-Shirley 2001a,b). Gene expression analysis in the y1 mutant and wild-type genotypes further revealed that the transcription of these biosynthetic genes is y1 dependent.…”
Section: Discussionmentioning
confidence: 99%